Analisis Kesulitan Mahasiswa Prodi Pendidikan Bahasa Jepang UNNES dalam Mengungkapkan Pendapat pada Mata Kuliah Kaiwa Enshuu Kegiatan Talkshow - Novia Andriyastuti; Rina Supriatnaningsih (Chi'e: Journal of Japanese Learning and Teaching, 2020)
Talkshow is one of the activities in the Kaiwa Enshuu course. In these activities, students are required to be able to express their opinions directly in accordance with a predetermined theme. Based on the results of the preliminary study, information was obtained that 34 of the 36 respondents were Japanese Language Education Study Program students in 2014 or 94.4% had difficulty expressing their opinions in talkshow activities. This study aims to determine the difficulties of students in expressing opinions talkshow activities, as well as the factors that cause difficulties and solutions to overcome difficulties. This research uses a quantitative descriptive approach. The subjects of this study were the 2014 Japanese language study program students who had taken and followed the Kaiwa Enshuu course. Data collection with a semi-open questionnaire. The results of the questionnaire were analyzed using the percentage formula. The results showed that students had difficulty in choosing the right and varied vocabulary (71.25 ï¼…), compiling effective sentences that had been learned ï¼ˆ71.25%ï¼‰. The difficulty factor is the shame factor for fear of making mistakes (70%). The solution to overcome the difficulties of lecturers motivates students to not be shy/reluctant to express their opinions so that students try to practice using Japanese both independently and in groups, besides motivating students to increase their confidence.